2018
DOI: 10.15557/jou.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between splenic length in healthy children from the Eastern Anatolia Region and sex, age, body height and weight

Abstract: PurposesThe normal limits of spleen size must be known in order for pathological changes to be noticed. The aim of this retrospective study is to determine the normal limits of spleen size in healthy children and to reveal their relation to sex, age, body height and weight.Patients and methodsThree hundred and ten children (150 girls and 160 boys) between 0–16 years of age in Eastern Anatolia Region who had normal spleen ultrasound appearances were included in this study. The greatest longitudinal distance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…Postoperative CT was proposed by the physician according to the clinical necessity. Since healthy human SV is correlated with individual weight and height, both in pediatric [17,18] and adult [19,20] patients, volumetric calculations of the spleen were normalized by BSA to eliminate the impact of patient size on SV. BSA was estimated according to the equation of Du Bois et al [21] as BSA (m 2 ) = body weight(kg) 0.425 x body height(cm) 0.725 x 0.007184, and the SV/BSA value was used as a parameter to evaluate the SV of patients.…”
Section: Spleen Volumetry Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative CT was proposed by the physician according to the clinical necessity. Since healthy human SV is correlated with individual weight and height, both in pediatric [17,18] and adult [19,20] patients, volumetric calculations of the spleen were normalized by BSA to eliminate the impact of patient size on SV. BSA was estimated according to the equation of Du Bois et al [21] as BSA (m 2 ) = body weight(kg) 0.425 x body height(cm) 0.725 x 0.007184, and the SV/BSA value was used as a parameter to evaluate the SV of patients.…”
Section: Spleen Volumetry Evaluationmentioning
confidence: 99%
“…The median interval between LT and postoperative laboratory tests was 1091 days with a range of 1029 to 1325 days. Patients who suffered from post-transplantation SM had significantly higher INR, AST and ALT (1.1 (1-1.2) vs. 1 (1-1.1); 31 vs. 24 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 23 (14-45) vs. 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), respectively) and markedly lower PLT and WBC (143 (89-189) vs. 203 (170-256); (5.2 (4-6.7) vs. 6.3 (5.1-7.7)) than the non-SM group.…”
Section: Long-term Consequences Of Post-transplantation Smmentioning
confidence: 99%
“…The 10 studies remaining for evaluation in this review were published between 1991 and 2018 (Figure ). Five studies included data of the liver, 6 of the spleen, and 4 of both kidneys …”
Section: Resultsmentioning
confidence: 99%
“…The studies included patients from 0 to 20 years of age; however, only data from those aged 0 to 18 years are included here because those 19 years and older are considered young adults. Two studies included patients from 0 to 18 years; 1 study included infants from 0 to 1 year; and the remainder included groups between 0 and 16 years …”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that spleen size correlates better with particular body parameters. 6 - 7 , 9 - 10 , 13 - 15 One study reported that body weight was better correlated with the longitudinal dimensions of the spleen than with the body surface area of pediatric subjects. 16 Another study found a significant correlation between height and splenic length.…”
Section: Introductionmentioning
confidence: 99%